“Ispeak” an Application to Improve student’s speaking competencies - Natasya Herza Harahap,; Maryati Salmiah, (RETORIKA: Jurnal Ilmu Bahasa, 2024)
The rapid progress of technology in recent years has introduced innovative approaches to education, enabling educators to leverage technology for teaching. This study examines the "Ispeak" application’s impact on junior high school students' speaking skills, specifically focusing on fluency, pronunciation, and vocabulary usage. The research aims to identify the specific features of the Ispeak application that enhance these aspects of speaking skills and explore its potential as an effective tool in technology-enhanced learning environments. Utilizing qualitative methods, the study collects and analyzes data through questionnaires, interviews, and documented sources. The findings reveal that the Ispeak application significantly supports English language learning by offering a flexible and cost-effective learning experience. Key to its effectiveness are the supportive role of teachers and the consistent use of the app by students, both of which contribute to improvements in speaking competencies.